Supplementation of Saussurea costus root alleviates sodium nitrite-induced hepatorenal toxicity by modulating metabolic profile, inflammation, and apoptosis - Elshaer, Samy E.; Hamad, Gamal M.; Sobhy, Sherien E.; Darwish, Amira M. Galal; Baghdadi, Hoda H.; H. Abo Nahas, Hebatallah; El-Demerdash, Fatma M.; Kabeil, Sanaa S. A.; Altamimi, Abdulmalik S.; Al-Olayan, Ebtesam; Alsunbul, Maha; Docmac, Omaima Kamel; et al. (Frontiers in Pharmacology, 2024)
Sodium nitrite (NaNO2) is a widely used food ingredient, although excessive concentrations can pose potential health risks. In the present study, we evaluated the deterioration effects of NaNO2 additives on hematology, metabolic profile, liver function, and kidney function of male Wistar rats. We further explored the therapeutic potential of supplementation with S. costus root ethanolic extract (SCREE) to improve NaNO2-induced hepatorenal toxicity. In this regard, 65 adult male rats were divided into eight groups; Group 1: control, Groups 2, 3, and 4 received SCREE in 200, 400, and 600 mg/kg body weight, respectively, Group 5: NaNO2 (6.5 mg/kg body weight), Groups 6, 7 and 8 received NaNO2 (6.5 mg/kg body weight) in combination with SCREE (200, 400, and 600 mg/kg body weight), respectively. Our results revealed that the NaNO2-treated group shows a significant change in deterioration in body and organ weights, hematological parameters, lipid profile, and hepatorenal dysfunction, as well as immunohistochemical and histopathological alterations. Furthermore, the NaNO2-treated group demonstrated a considerable increase in the expression of TNF-α cytokine and tumor suppressor gene P53 in the kidney and liver, while a significant reduction was detected in the anti-inflammatory cytokine IL-4 and the apoptosis suppressor gene BCL-2, compared to the control group. Interestingly, SCREE administration demonstrated the ability to significantly alleviate the toxic effects of NaNO2 and improve liver function in a dose-dependent manner, including hematological parameters, lipid profile, and modulation of histopathological architecture.Additionally, SCREE exhibited the ability to modulate the expression levels of inflammatory cytokines and apoptotic genes in the liver and kidney. The phytochemical analysis revealed a wide set of primary metabolites in SCREE, including phenolics, flavonoids, vitamins, alkaloids, saponins and tannins, while the untargeted UPLC/T-TOF-MS/MS analysis identified 183 metabolites in both positive and negative ionization modes. Together, our findings establish the potential of SCREE in mitigating the toxic effects of NaNO2 by modulating metabolic, inflammatory, and apoptosis. Together, this study underscores the promise of SCREE as a potential natural food detoxifying additive to counteract the harmful impacts of sodium nitrite.